Pengaruh Disiplin dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada Azo Florist Cianjur - Dewi Yuliati Indah; R. Dewi Puspasari (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The phenomenon that occurs the company is faced with the problem of employees how to make employees, to be able to work by showing good performance. One of the factors that affect employee performance is work discipline, besides that, another factor that can affect employee performance is organizational commitment. The purpose of this study was to determine the respondents' responses and the effect of discipline, organizational commitment on employee performance at Azo Florist Cianjur either simultaneously or partially. This research method is quantitative with multiple linear regression analysis. The number of samples is 50 employees and using a saturated sample. The results showed that employees' responses to discipline were not good, organizational commitment was not good and responses to performance were not good, then simultaneously discipline and organizational commitment contributed or influenced employee performance by 65.5% and the remaining 34.5% was contributions from other variables not included in the model proposed in this study. While the influence of the coefficient of determination partially, it is known that the effect of discipline on employee performance is 12.0%. Meanwhile, organizational commitment has a more dominant influence on employee performance by 53.5%.